2003
DOI: 10.1139/w03-062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variability of sunflower downy mildew,Plasmopara halstedii, from different continents

Abstract: Downy mildew of sunflower (Helianthus annuus L.), caused by the pathogen Plasmopara halstedii, is a potentially devastating disease. Seventy-seven isolates of P. halstedii collected in twelve countries from four continents were investigated for RAPD polymorphism with 21 primers. The study led to a binary matrix, which was subjected to various complementary analyses. This is the first report on the international genetic diversity of the pathogen. Similarity indices ranged from 89% to 100%. Neither a consensus u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Although downy mildew of sunflower (Plasmopara halstedii) can be effectively controlled by using resistant cultivars and⁄or by applying fungicides as seed treatment, protection can be hindered by the genetic variability of the fungus (Albourie et al 1998;Roeckel-Drevet et al 2003;Gulya 2007). Thus, there is a need for research into alternative methods of effective disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Although downy mildew of sunflower (Plasmopara halstedii) can be effectively controlled by using resistant cultivars and⁄or by applying fungicides as seed treatment, protection can be hindered by the genetic variability of the fungus (Albourie et al 1998;Roeckel-Drevet et al 2003;Gulya 2007). Thus, there is a need for research into alternative methods of effective disease control.…”
Section: Introductionmentioning
confidence: 99%
“…These two genes controlled the downy population in Europe until 1998 when new races emerged (710 and 703) in France (Tourvieille de Labrouhe et al, 1991). Later research showed that these races were introduced from the USA via infected seeds (Roeckel-Drevet et al, 2003). After the introduction of these races, there occurred a conflagration of new downy mildew races, especially in France.…”
Section: Resultsmentioning
confidence: 99%
“…Random amplified polymorphic DNA (RAPD) PCR markers studied by Borovkova et al (1992) were too sensitive and revealed differences even between isolates from the same virulence phenotype. However, in a study by Roeckel-Drevet et al (2003), RAPD-based analysis detected differences between isolates from distant geographical regions and showed low genetic variability among isolates in the same region, caused probably by bottleneck and founder effects. Intelmann & Spring (2002) performed RFLP studies of mitochondrial DNA and used simple sequence repeats and microsatellites as primers for the PCR.…”
Section: Intraspecific Variability Of P Halstediimentioning
confidence: 94%
“…However, in a study by Roeckel‐Drevet et al . (), RAPD‐based analysis detected differences between isolates from distant geographical regions and showed low genetic variability among isolates in the same region, caused probably by bottleneck and founder effects. Intelmann & Spring () performed RFLP studies of mitochondrial DNA and used simple sequence repeats and microsatellites as primers for the PCR.…”
Section: Characteristics Of the Pathosystem H Annuus–p Halstediimentioning
confidence: 95%